Annual Plan 1995-96 Statements Volume-II Government of Manipur - Planning Commission (Planning Commission, 1995)
Abstract of Financial Outlays and Expenditure for 8th Plan 1992-97 and Annual Plan 1995-96 Annual Plan 1995-96 Proposed Outlay - G.N. Statement Progress of Expenditure during the Annual Plan 1994-95 and Proposed Outlay for the Annual Plan 1995-95 Physical Targets and Achievement during the Annual Plan 1994-95and Proposal for the Annual Plan1995-96” Proposals for Spill over and Ongoing Programme/Projects Proposals for Maximising Benefits of Completed Programmes/Projects Proposals for Programmes/Projects New/ Schemes of Tight Plan Summary Statement- Proposals for Programmes/Projects Statement Regarding Externally Aided Projects Annual Plan 1995-96 Outlays By Heads of Development (For District Plans).
Government of Manipur, Planning Department